Roads to development? A comparison of development corridors vs regional roads in the Zambezi Region, Namibia - Justina Tuulikefo Nangolo; Christoph Hütt; Georg Bareth; Javier Revilla Diez (Journal of Maps)
Despite the increasing popularity of development corridors, their effectiveness in promoting regional development compared to regional roads remains uncertain. This study utilised satellite imagery to compare land use transformation within a 10km corridor effect zone along the Walvis Bay - Ndola - Lubumbashi Development Corridor (WBNLDC) and regional roads in Namibia's Zambezi Region. Overall, the Zambezi Region experienced a strong increase in built-up areas (+165%) and cultivated land (+136%) between 2000 and 2023 at the expense of forest (−18%) and grasslands (−18%). Cultivated and built-up areas expanded most intensively along regional roads, where most of the population resides, particularly after road tarring. This suggests regional roads drive land use change more effectively. The findings imply that local communities profit more from regional roads, and targeted investment in such infrastructures might be more beneficial to support the region's food basket goals and improve livelihoods rather than international corridors like the WBNLDC.